2018
DOI: 10.24106/kefdergi.2227
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmen Adaylarının Grafik Çiziminde Karşılaştıkları Güçlüklerin Belirlenmesi

Abstract: Bu çalışma, fen bilgisi öğretmen adaylarının çözünürlük konusunda grafik çizmede karşılaştıkları güçlükleri belirlemek amacıyla yapılmıştır. Betimsel tarama modeli kapsamında; sudaki çözünürlüğü sıcaklıkla değişen beş bileşiğin belirli sıcaklıklarda sudaki çözünürlükleri bir tablo halinde verilmiş ve çözünürlüksıcaklık grafiklerini çizmeleri öğretmen adaylarından istenmiştir. Çalışmaya, toplam 96 fen bilgisi öğretmen adayı gönüllü olarak katılmıştır. Elde edilen veriler, literatürde önceden belirlenmiş kriterl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Similarly, Hale (1996) indicated that students find it difficult to find displacement by looking at the velocity-time graph. One reason for their low level of skills related to graph reading-interpretation and drawing can be their lack of enough experience in using graphs (Ercan, Coştu & Coştu, 2018). There are studies in the literature indicating that students should have a certain knowledge of mathematics and subject/field knowledge (Demirci & Uyanık, 2009;Bayazıt, 2011;Bütüner & Uzun, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hale (1996) indicated that students find it difficult to find displacement by looking at the velocity-time graph. One reason for their low level of skills related to graph reading-interpretation and drawing can be their lack of enough experience in using graphs (Ercan, Coştu & Coştu, 2018). There are studies in the literature indicating that students should have a certain knowledge of mathematics and subject/field knowledge (Demirci & Uyanık, 2009;Bayazıt, 2011;Bütüner & Uzun, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It was noticed that at the very beginning of the misconceptions about graph drawings, pre-service teachers were inclined to draw linear graphs. Ercan et al (2018) emphasizes that if the merging of the dots appropriate lines is not done correctly, the tendency of the graph cannot be determined precisely, and it may cause a great mistake. Therefore, in this study, it was seen that this mistake emerged as an error in interpreting the graph.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that these students rarely pointed the dots and stated that they did not find it necessary to complete the line graph. Ercan et al (2018) stated that pre-service science teachers were similarly weak in presenting the expected performance in the criteria of axis scaling, correct placement of data pairs on the axis, and bounding the points in their study with pre-service science teachers. Yayla and Özsevgeç (2014) found a positive relationship between students' drawing and interpretation of graphs in their study with secondary school (6,7, and 8th grade) students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is discussed in the literature that pre-service science teachers cannot completely adopt student-centred methods (Yıldırım, Sürmeli, Benzer, & Şahin, 2007), their levels of scientific processing skills are low (Çakır & Sarıkaya, 2018;Önal, Büyük, & Saraçoğlu, 2017), therefore they have difficulty in transferring their subject matter knowledge to practice (Ercan, Coştu, & Coştu, 2018). Pre-service science teachers' cognitive awareness levels are not adequate (Emrahoğlu & Öztürk, 2010) and they have problems with scientific creativeness (Demirhan, Önder, & Beşoluk, 2018).…”
Section: Changes In General Competencies For Teaching Profession (Gctmentioning
confidence: 99%